2015
DOI: 10.1080/15389588.2015.1010722
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study on the Efficacy of Advanced Belt Restraints to Mitigate the Effects of Obesity for Rear-Seat Occupant Protection in Frontal Crashes

Abstract: Objective: Recent field data analyses have shown that the safety advantages of rear seats relative to the front seats have decreased in newer vehicles. Separately, the risks of certain injuries have been found to be higher for obese occupants. The objective of this study is to investigate the effects of advanced belt features on the protection of rear-seat occupants with a range of body mass index (BMI) in frontal crashes.Methods: Whole-body finite element human models with 4 BMI levels (25, 30, 35, and 40 kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Details about the RBF-TPS have been previous described by (Donato and Belongie, 2002). Similar methods have been used to build parametric FE models previously (Klein et al, 2015;Ma et al, 2011;Wang et al, 2015).…”
Section: Mesh Mappingmentioning
confidence: 99%
“…Details about the RBF-TPS have been previous described by (Donato and Belongie, 2002). Similar methods have been used to build parametric FE models previously (Klein et al, 2015;Ma et al, 2011;Wang et al, 2015).…”
Section: Mesh Mappingmentioning
confidence: 99%
“…A review of the test video revealed that the seatbelt was very close to the upper sternum and neck region due to the small stature of the ATD, which will likely lead to smaller chest deflection measures. Further studies using computational human models (Holmqvist et al 2014;Kimpara et al 2006;Wang et al 2015) may help us evaluate the chest deflections better.…”
Section: Discussionmentioning
confidence: 99%
“…An advanced seat belt system with shoulder or lap pretensioner can effectively reduce the body excursions, and a seat belt load limiter can reduce the chest deflection at the cost of increasing the head excursion in severe frontal crashes. Therefore, load limits that can adapt to occupants with different obesity levels are needed to protect the head and chest at the same time .…”
Section: Discussionmentioning
confidence: 99%